THE MIND - Wilson, John Rowan, 1919-1973, author 648484; Time-Life Books 11642 (New York, NY : Time-Life Books Inc., 1980)
Many sciences are contributing to an understanding of that elusive subject, "the mind," and the many of the findings are set forth in this volume. The emphasis, however, falls chiefly on two fields of scientific inquiry: neurobiology and psychology. In text chapters and picture essays, the book describes the anatomy of the nervous system and summarizes the most recent research into such subject as learning, intelligence, language and mental illness. It explores the implications of the new knowledge about mind and brain that is emerging from experimental laboratories around the world. Chapters of text alternate with picture essays that illustrate or complement the chapters, although each may be read independently. For example, Chapter 4, "Psychoanalysis: Delving into the Unconscious," is followed by a photographic album of the life of Sigmund Freud, the founder of the psychoanalytic method.